Recent advances in functionalization of copper and tin oxide nanomaterials for application in sensing : A comparative review - Kader, Md Ashraful; Nina Suhaity, Azmi; Kafi, A. K.M.; Alim, Samiul (Elsevier Ltd, 2024)
Sensors can detect various environmental parameters such as air quality, water quality, soil conditions, and more. They enable continuous monitoring, and early detection of pollutants, and help in assessing environmental health. With advancements, sensors could become more portable, cost-effective, and capable of detecting a wider range of pollutants with higher sensitivity. Copper and tin-based oxide nanomaterials are the most dynamic of such metal oxide nanomaterials that have been widely exploited in the development of chemical and gas sensors. Indeed, metal oxides, while catalytically active, can suffer from drawbacks such as limited selectivity and unstable reactivity, which can hamper sensor performance. Functionalization techniques involving various nanomaterials and conducting polymers are commonly employed by researchers to address the limitations associated with metal oxide-based sensors. This review covers the recent developments of functionalization of the most commonly used metal oxide nanomaterials derived from Cupric oxide (CuO), Cuprous oxide (Cu2O), Tin(II) oxide (SnO) and Tin(IV) oxide (SnO2) and their applications in the field of chemical and gas sensing. Cabbalistic data are displayed in the tables, and the review concludes with possibilities and difficulties related to metal oxide-based sensors are discussed.